Simultaneous Estimation of Domperidone and Pantoprazole in Solid Dosage Form by UV Spectrophotometry - P. Ravi Kumar; P. Bhanu Prakash; M. Murali Krishna; M. Santha Yadav; C. Asha Deepthi (E-Journal of Chemistry)
Domperidone is an antiemetic and pantoprazole is an antiulcer drug. Simple, precise, rapid and selective simultaneous equation and Q- analysis UV spectrophotometric methods have been developed for the simultaneous determination of domperidone and pantoprazole from combined tablet dosage forms. The methods involve solving of simultaneous equations and Q-value analysis based on measurement absorptivity at 216, 287 and 290 nm respectively. Linearity lies between 1-15 mcg/mL for domperidone and 0-50 mcg/mL for pantoprazole.